Ethics of the ordinary, amplified in the intensive care unit - Nurses' responses to moral distress experienced in their professional practice during the COVID-19 pandemic - Gehrke, Paige (My University, 2023)
Background: Nurses working in intensive care units are at high risk for experiencing moral distress, a response to an ethical event, in which a nurse recognizes or partakes in an action that does not align with their values. In response, nurses may experience negative health effects, which drives attrition. This can negatively impact patient care and the stability of healthcare organizations. There is a scarcity of high-quality and effective organizational interventions to mitigate moral distress, and even lesser work has been done to understand nurses’ practice-based needs to ameliorate moral distress. New conditions of moral distress in the context of COVID-19 have increased the relevance of these shortcomings. Aim: The purpose of this study was to learn about intensive care unit nurses’ responses to moral distress experienced in their professional practice during the COVID-19 pandemic. Methods: This interpretive descriptive study explored the experiences of 40 intensive care unit nurses, who self-reported experiencing moral distress in their professional practice during the COVID-19 pandemic (March 2020 – Sept 2021). Data generation included a demographic questionnaire, including the Measure of Moral Distress - Healthcare Professionals survey, and one-to-one semi-structured virtual interviews. The categorization and synthesis of the data was guided by methods of reflexive thematic analysis and rapid qualitative analysis. Results: Findings indicated that nurses regularly navigated pre-existing and novel ethical events in practice, which were exacerbated in the context of the COVID-19 pandemic. In response, they often experienced moral distress under the complex interplay of two overarching and broad conditions: (1) when nurses’ voices were not heard; and (2) when patients received substandard levels of care, that was not patient-centered, pain free, or that did not align standards of care. Moral distress experienced by nurses resulted in negative outcomes across serval health domains, that drove feelings of burnout and attrition. To cope, nurses engaged in patterns of action, avoidance, and acquiesce. Finally, they made recommendations for mitigative interventions rooted in their desire to be heard, in efforts to optimize patient care and nurse well-being. Conclusion: Intensive care unit nurses’ voices need to be amplified and valued, in the context of various healthcare organizations (e.g., practice, research, education and polity), to mitigate moral distress and the associated negative outcomes.
Keywords: Moral distress; Intensive care; Nurse; Critical care; Nursing ethics; COVID-19